The Influence of Competency, Professionalism and Auditor Independence on Audit Quality with Integrity as a Moderation Variable at DKI Jakarta Public Accounting Firm (Empirical Study at The Public Accounting Office of DKI Jakarta Province) - Sulaeman, Andri; Ismail, Tubagus; Mulyasari, Windu (PT. EQUATOR SINAR AKADEMIA, 2024)
This research aims to examine and analyze the influence of auditor competence, auditor professionalism, auditor independence on audit quality, which is moderated by integrity at Public Accounting Firms in DKI Jakarta. This research uses primary data in the form of a questionnaire with the research sample being employees of a public accounting office in DKI Jakarta. The population used in this research were all auditors working at the Public Accounting Firm (KAP) of DKI Jakarta Province, with a total of 260 registered KAPs. The sampling technique in this research used the purposive sampling method. In this research, the analytical techniques used were validity testing, reliability testing and hypothesis testing with the help of a statistical application in the form of Smart PLS 4.The research results show that the relationship between competency (X1) and audit quality (Y) has a t statistics value of 2,226 > 1.96 with a p value of 0.000, meaning that H1 is accepted. The relationship between auditor professionalism has a t statistic of 2,320 > 1.96 with a p value of 0.000, meaning that H2 is accepted. The relationship between auditor independence has a t statistic of 2.226 > 1.96 with a p value of 0.000, meaning that H3 is accepted. That the auditor integrity variable moderating auditor competence, auditor professionalism and auditor independence on audit quality has a t statistical value of 2.336 > 1.96, meaning that H4, H5, H6 are accepted.